A Highly Selective 3D Spiked Ultraflexible Neural (SUN) Interface for Decoding Peripheral Nerve Sensory Information. Issue 5 (4th December 2017) - Wang, Jiahui; Thow, Xin Yuan; Wang, Hao; Lee, Sanghoon; Voges, Kai; Thakor, Nitish V.; Yen, Shih‐Cheng; Lee, Chengkuo
Abstract: Artificial sensors on the skin are proposed as a way to capture information that can be used in intracortical microstimulation or peripheral intraneural stimulation to restore sensory feedback to persons with tetraplegia. However, the ability of these artificial sensors to replicate the density and complexity of the natural mechanoreceptors is limited. One relatively unexplored approach is to make use of the signals from surviving tactile and proprioceptive receptors in existing limbs by recording from their transmitting axons within the primary sensory nerves. Here, a novel spiked ultraflexible neural (SUN) interface that is implanted into the peripheral nervous system to capture sensory information from these mechanoreceptors in acute rat experiments is described. The novel 3D design, which integrates spiked structures for intrafascicular nerve recording with an ultraflexible substrate, enables a unique conformal interface to the target nerve. With the high‐quality recording (average signal‐to‐noise‐ratio of 1.4) provided by the electrode, tactile from proprioceptive stimuli can be differentiated in terms of the firing rate. In toe pinching experiments, high spatial resolution classification can be achieved with support vector machine classifier. Further work remains to be done to assess the chronic recording capability of the SUN interface. Abstract : A spiked ultraflexible neural interface is successfully used to record sensory signal from the peripheral nervous system. The 3D spiked electrodes enable intrafascicular access to nerve fascicles, while the flexible substrate enables conformal contact with the nerve. With the excellent recording capabilities of this neural interface, different types of sensory signals, as well as signals from different parts of the body, are differentiated successfully.